2018
DOI: 10.1111/bdi.12639
|View full text |Cite
|
Sign up to set email alerts
|

Genes involved in stress response influence lithium efficacy in bipolar patients

Abstract: The response to lithium may depend on the variants of genes regulating the HPA axis and stressful life events in bipolar patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
6
0
2
Order By: Relevance
“…For coping, functions relating to behaviour were identified for six of the 11 genes: GABARAP (Hui et al., 2019), NDM (Costilla et al., 2020), OAZ1 (Fiori et al., 2012), RPS15A (Park et al., 2011), SPARCL1 (Seddighi et al., 2018) and VAMP2 ( Zhang et al., 2021). For cortisol, functions relating to behaviour were identified for five of the 14 genes: CEBPA (Chen et al., 2020), COA3 (Liu et al., 2021), DUSP1 (Horita et al., 2010; Jefsen et al., 2021; Juszczak & Stankiewicz, 2018; Szczepankiewicz et al., 2018; Takemoto et al., 2020; Zhao et al., 2017), HNRNPH1 (Gillentine et al., 2021) and RACK1 (Birikh et al., 2003; Corcoran et al., 2015; McGough et al., 2004; Neasta et al., 2012). The majority of the genes were associated with phenotypes observed in humans and mice such as social behaviour ( GABARAP ), autism spectrum disorder ( NDM ), suicide ( OAZ1 ), Alzheimer's disease ( SPRCL1 ), stress‐induced anxiety and depression ( COA3 , DUSP1 , VAMP2 ), neurodevelopmental disorders ( HNRNPH1 ), neuroinflammatory disease ( CEPBA ), fear‐induced behaviours ( RPS15A , RACK1 ), and alcohol and cocaine addiction ( RACK1 ).…”
Section: Discussionmentioning
confidence: 99%
“…For coping, functions relating to behaviour were identified for six of the 11 genes: GABARAP (Hui et al., 2019), NDM (Costilla et al., 2020), OAZ1 (Fiori et al., 2012), RPS15A (Park et al., 2011), SPARCL1 (Seddighi et al., 2018) and VAMP2 ( Zhang et al., 2021). For cortisol, functions relating to behaviour were identified for five of the 14 genes: CEBPA (Chen et al., 2020), COA3 (Liu et al., 2021), DUSP1 (Horita et al., 2010; Jefsen et al., 2021; Juszczak & Stankiewicz, 2018; Szczepankiewicz et al., 2018; Takemoto et al., 2020; Zhao et al., 2017), HNRNPH1 (Gillentine et al., 2021) and RACK1 (Birikh et al., 2003; Corcoran et al., 2015; McGough et al., 2004; Neasta et al., 2012). The majority of the genes were associated with phenotypes observed in humans and mice such as social behaviour ( GABARAP ), autism spectrum disorder ( NDM ), suicide ( OAZ1 ), Alzheimer's disease ( SPRCL1 ), stress‐induced anxiety and depression ( COA3 , DUSP1 , VAMP2 ), neurodevelopmental disorders ( HNRNPH1 ), neuroinflammatory disease ( CEPBA ), fear‐induced behaviours ( RPS15A , RACK1 ), and alcohol and cocaine addiction ( RACK1 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] First, recent studies have reported an association of FKBP5 SNPs with treatment response in affective disorders. One study of 93 patients with bipolar disorder reported that SNPs rs1360789, rs9296158, and rs7748266, were associated with lithium response, [ 41 ] whereas the TT genotype of rs1360789 was shown to be associated the response to antidepressant treatments in a STAR∗D cohort. [ 42 ] Secondly, some variants of the FKBP5 gene were also shown to be associated with the susceptibility for depression.…”
Section: Discussionmentioning
confidence: 99%
“…They have been those connected with neurotransmitters—serotonin transporter, dopamine D1 receptor ( DRD1 ) genes, second messengers (inositol polyphosphate 1‐phosphatase, CREB1 genes), glycogen synthase kinase 3‐β ( GSK‐3β ) gene, brain‐derived neurotrophic factor ( BDNF ) gene, glucocorticoid receptor ( NR3C1 ) gene, in circadian rhythms ( Rev‐Erba‐α gene), and genes located on chromosome 22q11‐13 (breakpoint cluster region— BCR , X‐box binding protein 1— XBP1 , and the calcium channel gamma‐2 subunit— CACNG2 ) genes (Rybakowski, 2013). Related to the role of stress factors, we found an association between prophylactic lithium efficacy and the genes connected with stress axis such as glucocorticoid receptor ( NR3C1 ) gene) and FKBP5 gene (Szczepankiewicz et al, 2018; Szczepankiewicz, Rybakowski, Suwalska, & Hauser, 2011).…”
Section: Personalized Medicine and Lithium Prophylaxis: Biological Factorsmentioning
confidence: 99%